CURRENT ISSUES OF TRAINING UNDER THE CREDIT-MODULAR SYSTEM - Umarova Dilfuza Satvoldievna (European Science Publishing, 2024)
This article highlights some problems and prospects in training when applying the credit-module system (CMS) in higher education. Let's consider the advantages and limitations of this system, as well as its impact on the organization of the educational process and assessment of student performance. The key factors that determine the effectiveness of training and the quality of education received in the context of CMS are analyzed.
Keywords: credit-module system, higher education, performance assessment, flexibility of the educational process, standardization of programs.